Mapeamento de solos através do caráter espectral, da rede de drenagem e da vegetação - Marchetti, D.a. (1990)
This study puts together three different methodologies that utilize Remote Sensing Techniques for the study of soils. The soils of the selected area were studied by their spectra parameters and analysed through satellite images processed in an appropriate equipment. The drainage indices were correlated to their respective soils. The well known relationship between types of cerrado vegetation and associated soils were also studied. For each situation a soil map was prepared; those maps showed a reasonable relationship with the ground truth. Wen these informations were put together in a single map, the relationship with the reference soil map was highly significant, showing the applicability of the methodology.